Diagnostic yield of tuberculosis investigations on bone marrow biopsy samples in HIV positive patients at Groote Schuur Hospital - Baloyi, Xikombiso (Department of Clinical Laboratory Sciences, 2024)
Background: Acid fast bacilli (AFB) staining on bone marrow samples has low sensitivity for diagnosing HIVassociated tuberculosis and Tuberculosis (TB) culture results may be delayed. The GeneXpert® MTB/RIF Ultra assay may provide a more sensitive diagnostic test on bone marrow biopsy samples. Methods: We conducted a two-stage study in a tertiary hospital in South Africa, initially assessing the retrospective yield of TB diagnoses on bone marrow biopsies in adult HIV-positive participants retrospectively from 01-01-2019 to 31-07-2020. Subsequently, determining the prospective yield and diagnostic performance of the GeneXpert® MTB/RIF Ultra assay on bone marrow aspirate and peripheral blood samples in adult HIV-positive participants undergoing bone marrow biopsy from 11- 08-2020 to 31-01-2021. Results: One hundred and twenty-two biopsies were analysed, of which 59/122 were performed for haematological malignancy staging. Granulomata with AFB were detected in six samples, and nine new lymphoma diagnoses were made. Bone marrow TB culture detected only one non-tuberculous mycobacterial infection. All 17 participants who had TB diagnosed from another clinical site were bone marrow TB culture negative. TB treatment was confirmed in 11/33 participants recruited prospectively. One trace positive GeneXpert® MTB/RIF Ultra result on peripheral blood was detected. All TB cultures on bone marrow aspirates and peripheral blood were negative. Conclusion: In a tertiary care hospital in South Africa, the utility of TB culture and GeneXpert® MTB/RIF Ultra on bone marrow aspirate specimens in HIV-positive participants was limited. We postulate that the initiation of empiric anti-tuberculosis treatment could have resulted in false negative results.